Experimental investigation on shear resistance of self-consolidating concrete beams - SAVARIS,G. (2019)
Abstract Self-consolidating concrete stands out for its high fluidity and stability, which are obtained by the reduction of the coarse aggregate dimensions and content in the mixture and also by the addition of superplasticizer and viscosity modifiers. An experimental test program was carried out to evaluate the influence of these particularities of self-consolidating concrete mixtures on the shear capacity of beams with shear reinforcement. Four mixtures of self-compacting concrete and two mixtures of conventionally vibrated concrete with different coarse aggregate size and volume were used for the production of beams to be tested under flexure. The experimental results were compared to those estimated by the ACI-318, CAN A23.3, EC-2 and NBR 6118 design codes. The results demonstrated that the reduction of coarse aggregate dimensions and content in self-compacting concrete mixture did not significantly influence the ultimate shear strength. The shear strengths obtained experimentally were considered adequate to codes estimates, for both concrete types.